(3GdbWY hGdEFJfGas - (3CMeO Hf eMeO Hf ESeGYjd GdeUQj GdfMhj, CHh LYaQ , GHf GdfMGS, J (B338 (3g` s ((3eMeO Hf ehSi Hf YeQGf s)
(3ChdgG (B:s
(3bGd CHh LYaQ CMeO Hf eMeO GdfMhi (B: (3GdMeO ddg GdPi GaJJM HGdMeO cJGHg hLYd dCfgd GdYde Phi GdYed KhGg bGd GHh LYaQ hgG GdcJGH GPcQ ajg GdJeGe ai GdbQGQGJ s
(3BNQgG (B:s
(3hMLJgG Cfg Udi Gddg Ydjg hSde CeQ Cf jbhd gPG cdg hcPG bd CYhP HQH Gdadb hbd CYhP HQH GdfGS hGddg CYde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B208s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs